2018
DOI: 10.1111/jir.12487
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and topographies for self‐injurious behaviour in a sample of adults with intellectual developmental disorders

Abstract: Knowledge on risk factors and topographies of SIB might play a vital role in the development of prevention strategies and management of SIB in people with IDD. The mere presence of ASD symptoms, regardless of its severity level, can be a crucial factor to be taken into account in assessing SIB. Accordingly, the presence of SIB in people with ID, especially when presented with a varied number of topographies, might provide guidance on ASD differential diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 52 publications
1
38
0
Order By: Relevance
“…Only two studies reported prevalence of self-injury across different levels of autism. These studies found that severity of autism is associated with a higher prevalence of self-injury, and moreover, that severity of self-injurious behaviour is associated with more severe autism (Akram et al 2017 ; Folch et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two studies reported prevalence of self-injury across different levels of autism. These studies found that severity of autism is associated with a higher prevalence of self-injury, and moreover, that severity of self-injurious behaviour is associated with more severe autism (Akram et al 2017 ; Folch et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sample AUTISM ID:IQ ID:AF SIB/SH Folch et al, (2018) 37.3 31.6 -- Gulsrud et al, (2018) 29.1 9 .0 25 -2 . 0 0.…”
Section: Authormentioning
confidence: 99%
“…Two studies 41 , 50 used the Diagnostic Assessment for the Severely Handicapped Part 2 (DASH-II) 65 . Two studies 43 , 53 used the Aberrant Behaviour Checklist-Community version (ABC-C) total score, 66 and another four 42 , 46 , 52 , 67 used ABC-C subdomain scores 68 . Three studies 37 , 38 , 69 used the Psychosocial Behaviour Scale (PBS) 70 .…”
Section: Resultsmentioning
confidence: 99%
“…The overall rate of challenging behaviour Of the total 19 controlled studies, 13 12,36,37,39,40,[43][44][45]47,[50][51][52][53] did not show any significant intergroup difference in the overall rate of challenging behaviour, three 38,42,48 showed a significantly higher rate of challenging behaviour in the epilepsy group and three 41,46,49 showed a higher overall rate of challenging behaviour in the non-epilepsy group (Table 1). Of these three, one 41 was at a significant level and the level of significance for other two 46,49 is not known.…”
Section: Outcome (Narrative Synthesis)mentioning
confidence: 97%
See 1 more Smart Citation